2019
DOI: 10.3390/su11154133
|View full text |Cite
|
Sign up to set email alerts
|

Green Development Behavior and Performance of Industrial Enterprises Based on Grounded Theory Study: Evidence from China

Abstract: The issue of the green development of industrial enterprises has become the focus of attention of all parties. However, the driving factors of green development behavior and performance in industrial enterprises remains unexplored. What are the driving factors of green development behavior and performance in industrial enterprises? How does the theoretical model of green development behavior and performance in industrial enterprises work? In order to reveal the driving factors of green development behavior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 25 publications
4
45
0
1
Order By: Relevance
“…Li et al found that the GD of industrial enterprises has become the focus of attention of all parties [12]. There are some researchers that have explored the driving factors of GD behavior and performance in enterprises.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al found that the GD of industrial enterprises has become the focus of attention of all parties [12]. There are some researchers that have explored the driving factors of GD behavior and performance in enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…They found some key factors, such as environmental education, external environmental pressures and opportunities, policy opportunities, market environment and public supervision, etc. [12][13][14][15]. The GD performance of industrial enterprises includes corporate financial performance, corporate environmental performance, and corporate social performance [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory of green development behavior and performance of industrial enterprises (GDBP-IE) [23,[58][59][60][61][62][63][64][65][66][67][68][69][70][71] Clean production behavior [23,[58][59][60][61][62][63][64][65] Green supply chain management practice [23,[66][67][68][69][70][71] Green development performance of industrial enterprises (GDP-IE)…”
Section: Fields Theoretical Basis Main Points Referencesmentioning
confidence: 99%
“…Grounded theory has been widely recognized and applied in many fields since it was put forward, including medical sociology, nursing, education, and management theory [57]. Li et al [58] have revealed the driving factors of green development behavior and the performance in industrial enterprises based on the grounded theory. By using a grounded theory approach, Liu et al [59] analyzed the qualitative data to explore project professionals' understandings of BIM application in collaborative design and construction.…”
Section: Grounded Theorymentioning
confidence: 99%